The Effect of Personal Resources and Job Resources on Work Engagement - A Study of a Multi-National Company Manufacturing Unit - Narjis, Mohamad Zaki (2011)
The purpose of this study is to investigate a business-unit work engagement and resources affecting its organizational success. The study is to examine and gain better understanding of the drivers that affects the work engagement at a multi-national company manufacturing unit located at Kulim Hi-Tech Park. The result of this study is to contribute to the research literature and help senior leaders focus on human capital strategies that produce returns on their investments. This study was done among 105 exempt staff of a manufacturing unit. Data were gathered through hardcopy questionnaires and was being analyzed using Statistical Package for Social Science (SPSS) version 16. Throughout the statistical analysis - correlation analysis, it was found that there is significant relationship between the two independent variables namely Personal Resources and Job Resources with dependent variables of Work Engagement. Among the two independent variables, job resources were found to be the most independent variable in driving the work engagement in this business unit.